Estimating the chemical composition of secondary compounds of Iraqi wild Agaricus bellaniae characterized morphologically and genetically (Baghdad Science Journal, 2023)
This study, which is considered the first of its kind in the world and the Arab homeland, was carried out in the laboratory of mushroom production belonging to the Medicinal Plant Unit/ College Of Agricultural Engineering Sciences/ University of  Baghdad during the period from July 21, 2016, to December 30, 2018, aiming to isolate and purify the mycelium of the wild isolation in addition to the genetic and morphological identification of the mushroom Agaricus bellaniae. The obtained pure isolation was tagged in the American National Center for Biotechnology Information (NCBI) with symbol MF987843.1, thus Iraq would be the second country in the world in which the mushroom is grown following the United States of America. The optimum temperature for the mycelium growth rate was also determined in the laboratory, as they ranged between 50 -60 ◦C. Furthermore, the dried fruit bodies were recognized qualitatively and quantitatively to identify their content of medicinally active compounds. Theyhave shown a high percentage of  Linoleic acid (47.77%), total anti-oxidants, and total phenols in addition to the high content of essential chemicals including high protein percentage (44%), mineral elements- selenium in particular (0.369 ppm), and amino acid where glutamic and aspartic acids recorded the highest percentage, reached 4.02% and 2.226% respectively.